Dampak Penggunaan Sistem Informasi Manajemen Terhadap Kinerja Pengawai DPUPR Kabupaten Padang Pariaman - ive, arivetullatif; Junaidi, Junaidi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The advent of information technology has significantly impacted organizational performance by leveraging management information systems to address existing challenges. Notably, employee performance decline poses a substantial issue. Organizations lacking management information systems exhibit diminished employee performance, potentially leading to deviations and dissatisfaction. This study employed saturated sampling with 60 respondents and questionnaire distribution. SPSS-based data analysis revealed a statistically significant relationship between management information systems (X) and employee performance (Y), with Sig. < 0.05 (Sig. 0.00 < 0.05). The findings underscore the pivotal role of management information systems in enhancing employee performance.